Improving of Design Parameters of an Industrial Continuous Catalytic Reforming Reactors - Hameed, Shymaa Ali (Iraqi Journal of Chemical and Petroleum Engineering, 2017)
Catalytic reforming of naphtha occupies an important issue in refineries for obtaining high octane gasoline and aromatic compounds, which are the basic materials of petrochemical industries. In this study, a novel of design parameters for industrial continuous catalytic reforming reactors of naphtha is proposed to increase the aromatics and hydrogen productions. Improving a rigorous mathematical model for industrial catalytic reactors of naphtha is studied here based on industrial data applying a new kinetic and deactivation model. The optimal design variables are obtained utilizing the optimization process in order to build the model with high accuracy and such design parameters are then applied to get the best configuration of this process by new design variables. New results related to aromatic and hydrogen production have been obtained (the highest hydrogen and aromatic) in comparison with those reported in the literature and with the conventional method.